2013
DOI: 10.1021/tx400224j
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Aminoglutethimide on Neutrophils in Rats: Implications for Idiosyncratic Drug-Induced Blood Dyscrasias

Abstract: Aminoglutethimide (AMG) is an aromatic amine aromatase inhibitor associated with a high incidence of idiosyncratic blood dyscrasias, especially agranulocytosis. Animal models of idiosyncratic drug reactions (IDRs) represent essential tools to study these reactions; however, there is currently no valid model of idiosyncratic drug-induced agranulocytosis. Although AMG does not cause agranulocytosis in most animals or humans, drugs associated with serious IDRs generally cause a higher incidence of mild reactions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…This discrepancy could involve differences in the covalent binding of the reactive metabolite, or it could be totally independent of reactive metabolite formation. Together with the finding that other drugs that cause agranulocytosis also cause neutrophilia in rats, specifically aminoglutethimide and amodiaquine (unpublished observation), this suggests that the ability of a drug to induce neutrophilia may represent a biomarker of agranulocytosis risk. The accompanying article investigates the effects of clozapine on bone marrow and inflammatory markers in more detail.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…This discrepancy could involve differences in the covalent binding of the reactive metabolite, or it could be totally independent of reactive metabolite formation. Together with the finding that other drugs that cause agranulocytosis also cause neutrophilia in rats, specifically aminoglutethimide and amodiaquine (unpublished observation), this suggests that the ability of a drug to induce neutrophilia may represent a biomarker of agranulocytosis risk. The accompanying article investigates the effects of clozapine on bone marrow and inflammatory markers in more detail.…”
Section: Discussionmentioning
confidence: 70%
“…8 We found that clozapine also causes an increase in the release of neutrophils from the bone marrow and total neutrophil count in rabbits as well as a shortened neutrophil half-life. 9 An increase in neutrophils has also been observed in rats treated with aminoglutethimide, 10 which is also associated with a relatively high risk of drug-induced agranulocytosis. This suggests that these early changes in neutrophil kinetics could be a biomarker to predict the risk that a drug would cause agranulocytosis.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Considering 59% of small-molecule pharmaceuticals containing at least one N -heterocycle, the late-stage decorations of bioactive compounds were further evaluated. As shown in Scheme , aminoglutethimide, a steroidogenesis inhibitor, used in the treatment of Cushing’s syndrome, could be selectively inserted in an isoquinoline fragment to give product 81c in 53% yield. 4-Aminophenyl- d -galactopyranoside, a biologically relevant glycoside, afforded the desired product in 35% yield ( 82c ).…”
Section: Results and Discussionmentioning
confidence: 99%